Синтез субоптимальноного управления, расширяющего область притяжения управляемого объекта - Кудин, Валерий Федорович; Колесниченко, Сергей Петрович (НТУ "ХПИ", 2013)
The extremely important task of suboptimal regulator synthesis dilating the domain of the controlled object’s attraction is solved in the report. The decision of a task is based on Bellman – Lyapunov's method taking into account the principle of decomposition. The functional, considering the restrictions on the control and formulating the requirements to improve the transient process' quality is offered. The closed system simulation with a synthesized regulator is performed and showed an essential expansion of the domain of аattraction.
Keywords: теория автоматического управления; неустойчивость управляемого объекта; субоптимальный регулятор; оптимизация неквадратичного функционала